2004
DOI: 10.1007/s00122-004-1845-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular markers linked to papaya ring spot virus resistance and Fusarium race 2 resistance in melon

Abstract: In melon, the Fom-1 gene confers monogenic resistance against the soil-borne fungus Fusarium oxysporum f. sp. melonis, races 0 and 2, while the closely linked Prv gene specifies resistance against the papaya ring spot virus. Markers linked to these resistance (R) genes were identified using two recombinant inbred line populations, derived from crosses between Cucumis melo Vedrantais and C. melo PI 161375, and between C. melo Vedrantais and C. melo PI 414723, respectively. Using bulked segregant analysis, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 31 publications
2
52
0
Order By: Relevance
“…conglutinans) which is linked to fusarium wilt resistance were developed in cabbage by Lv et al (2013). There are studies that reported SCAR markers linked to Fox resistance in melon (Brotman et al 2005), cotton (wang et al 2009), ginger (Swetha and Subramanian 2008), chickpea (Sharma et al 2004) and eggplant (Mutlu et al 2008). SCAR markers associated with resistance to Foc4 were developed by wang et al (2010) for banana, namely ScaU1001 and ScaS0901 which amplified in Foc4-resistant banana genotypes but not in susceptible genotypes tested.…”
Section: Breeding/biotechnological Aspects Of Developing Tolerant Culmentioning
confidence: 99%
“…conglutinans) which is linked to fusarium wilt resistance were developed in cabbage by Lv et al (2013). There are studies that reported SCAR markers linked to Fox resistance in melon (Brotman et al 2005), cotton (wang et al 2009), ginger (Swetha and Subramanian 2008), chickpea (Sharma et al 2004) and eggplant (Mutlu et al 2008). SCAR markers associated with resistance to Foc4 were developed by wang et al (2010) for banana, namely ScaU1001 and ScaS0901 which amplified in Foc4-resistant banana genotypes but not in susceptible genotypes tested.…”
Section: Breeding/biotechnological Aspects Of Developing Tolerant Culmentioning
confidence: 99%
“…The first molecular markers linked to this gene, were reported by Brotman et al (2002Brotman et al ( , 2005 using two recombinant inbred line populations developed at ''Institut National de la Recherche AgronomiqueFrance'' (INRA). Based on BSA, Brotman et al (2005) identified a RAPD marker that generated a 1,235-bp fragment linked to the Fom-1 gene in repulsion phase.…”
Section: Molecular Markers Linked To Fom-1 Genementioning
confidence: 99%
“…Based on BSA, Brotman et al (2005) identified a RAPD marker that generated a 1,235-bp fragment linked to the Fom-1 gene in repulsion phase. This RAPD was converted to a CAPS marker designated as 62-CAPS (Table 3).…”
Section: Molecular Markers Linked To Fom-1 Genementioning
confidence: 99%
“…In melon, for example, there have been reports of linkage between molecular markers and resistance genes to Fusarium oxysporum f. sp. melonis (Wechter and Dean, 1998;Karsies et al, 2000;Brotman et al, 2005), zucchini yellow mosaic virus (ZYMV: Danin-Poleg et al, 2002), melon necrotic spot virus (MNSV: Baudracco-Arnas and Pitrat, 1996), cucumber mosaic virus (CMV; Dogimont et al, 2000), and papaya ringspot virus-W (PRSV-W: Brotman et al, 2005;Teixeira and Camargo, 2006). In addition, two candidate resistance genes have been identified by positional cloning, one conferring resistance to race 2 of F. oxysporum f. sp.…”
Section: Melonmentioning
confidence: 99%